Surgical treatment in children missed Monteggia lesions at Bhuj, Kutch, Gujarat: a retrospective study - Chauhan, Prakash (International Journal of Research in Orthopaedics, 2016)
Background: The treatment of an unrecognized Monteggia lesion continues to pose a therapeutic challenge, as evidenced by the variety of surgical techniques described. Moreover, there are high complication and redislocation rates following surgery. This report concerns a surgical technique to reduce a chronic dislocation of the radial head utilizing an ulnar osteotomy and internal fixation. Methods: Present study was performed at department of orthopedics, Gujarat Adani institute of medical science, Bhuj, Kutch, Gujarat. Ethical clearance was taken from the institutional ethics board and informed consent was obtained from all the participants. Between July 2015 and September 2016 six children presented in a traumatic context with chronic dislocation of the radial head and malunion of the ulna. Patient mean age was 6.5 (range 4–8) years, and the mean interval between injury and surgical procedure was 17 (range 1–49) months. Surgery consisted of an ulnar osteotomy with angulation and lengthening, bone grafting at the osteotomy site, and internal fixation. Open reduction of the radial head, repair or reconstruction of the annular ligament or temporary fixation of the radial head with a transarticular wire was not undertaken. Cast immobilization with the forearm in neutral rotation was maintained for 4-6 weeks. Results: There was one case of nonunion. At an average follow-up of 3 (range 1.5–4.4) years, all patients had regained painless function of the forearm, good range of elbow and forearm motion, and maintenance of the radial head reduction. Conclusions: Both angulation and elongation of the ulna are required to allow for reduction of the radial head. We do not see any indication for procedures directed at the radio-capitellar joint.